POSITIVE FEATURES OF THE RELATIONSHIP OF TOLERANCE IN EARLY ADOLESCENCE - Mubarak Qurbanova Bo'ybo'tayevna (American Journals Publishing, 2023)
In this article, the positive characteristics of tolerance relations in the period of early adolescence, and the shift in self-awareness are clearly visible in adolescents.
Keywords: Adolescence, Tolerant, opinion, feelings, Individual.